2005
DOI: 10.1007/s11249-005-6148-2
|View full text |Cite
|
Sign up to set email alerts
|

Tribofilms generated from ZDDP and DDP on steel surfaces: Part 1, growth, wear and morphology

Abstract: The growth and morphology of tribofilms, generated from zinc dialkyldithiophosphate (ZDDP) and an ashless dialkyldithiophosphate (DDP) over a wide range of rubbing times (10 s to 10 h) and concentrations (0.1-5 wt% ZDDP), have been examined using atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS) and X-ray absorption near edge structure (XANES) spectroscopy at the O, P and S K-edges and the P, S, and Fe L-edges. The physical aspects of the growth and morphology of the tribofilms will be pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 37 publications
(51 reference statements)
9
34
0
Order By: Relevance
“…These results can be explained by considering other published results, which showed that the morphology of ZDDP derived tribofilms evolves with rubbing time to become smoother and more uniformly distributed [15,23].…”
Section: Resultssupporting
confidence: 52%
“…These results can be explained by considering other published results, which showed that the morphology of ZDDP derived tribofilms evolves with rubbing time to become smoother and more uniformly distributed [15,23].…”
Section: Resultssupporting
confidence: 52%
“…----Authors of the current manuscript recently reported a theoretical model with a hypothesis that formation and removal of the tribofilm happen simultaneously [35]. The hypothesis was based on the experimental observations of removal of the tribofilm and wear of the system even in the presence of fully-formed tribofilms [17,31,36]. The wear hypothesis was then validated against some wear measurements in experiments [37,38] and has shown good agreement.…”
Section: Growth Of Zddp Tribofilmmentioning
confidence: 80%
“…The growth of ZDDP tribofilm on contacting surfaces has been subject of several studies [13,19,[27][28][29][30][31]. Fujita et al [32,33] studied the growth of ZDDP tribofilm using a Mini Traction Machine (MTM) and Spacer Layer Interferometry Method (SLIM).…”
Section: Growth Of Zddp Tribofilmmentioning
confidence: 99%
“…It was reported experimentally [16,[44][45][46] that, even in the areas where the tribofilm is fully formed, wear is occurring. It can be interpreted as partial removal of the tribofilm and at the same time formation of the film to restore the balance.…”
Section: Wear Modellingmentioning
confidence: 99%